Soluciones de la Ecuación de Smoluchowski caso discreto y caso continuo (2020)
In this work solutions of the discrete version Smoluchowski equation are presented using some probability concepts and methods to solve partial differential equations. The procedure to arrive at the solution of the Smoluchowski Equation continuous case is also shown, making use of some concepts of measurement theory when this equation has a constant nucleus. In addition, some results of great importance are presented in which the relationship between the equation with multiplicative nucleus and additive nucleus in the continuous version is highlighted. This equation is of great importance since it models the rate of change of the average number of polymers of mass k with respect to time t and also does not have to be solved using traditional methods due to its difficulty, which is why it is of great importance for mathematicians as it opens new paths for the solution of different types of equations.